2017
DOI: 10.3390/nu9080862
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Associations between a Locally Validated Mediterranean Diet Index, Overweight/Obesity, and Metabolic Syndrome in Chilean Adults

Abstract: Obesity and metabolic syndrome (MetS) are key risk factors for chronic disease. Dietary patterns are critical in the incidence and persistence of obesity and MetS, yet there is few data linking diet to obesity and MetS in Chile. Our objective was to use a locally validated diet index to evaluate adherence to a Mediterranean dietary pattern and its correlations with overweight/obesity (OW/O) and MetS prevalence in Chilean adults. We conducted a nationwide, cross-sectional online survey of Chilean adults with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 47 publications
2
39
0
1
Order By: Relevance
“…Recent studies [13,14] support, that a better adherence to MedDiet may play an important role in decreasing the incidence of obesity and metabolic syndrome. In this study better adherence to MedDiet was significantly associated with the lower waist circumference of the women.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies [13,14] support, that a better adherence to MedDiet may play an important role in decreasing the incidence of obesity and metabolic syndrome. In this study better adherence to MedDiet was significantly associated with the lower waist circumference of the women.…”
Section: Discussionmentioning
confidence: 95%
“…Large-scale projects demonstrated that the advantageous effects on the well-being of the participants seem to be attributed mainly to healthy mono-unsaturated fatty acids in 6 olive oil and flavonoids in red wine, nuts, spices etc [8][9][10][11]. These effects are accomplished through the anti-inflammatory and anti-oxidative actions of these components, leading to the decrease of inflammation and oxidative stress [8].…”
Section: Special Features Of the Mediterranean Diet And Links To Disementioning
confidence: 99%
“…Research conducted over the last two decades has consistently shown that adherence to MedDiet is beneficial for prevention or amelioration of numerous inflammatory diseases. The lion's share of the studies underlines the significant role of the Mediterranean dietary pattern in preventing cardiovascular diseases [9], type II Diabetes [10], obesity and metabolic syndrome [11,12]. Moreover, increased interest in the diet's results on human morbidities underscores the effect of prolonged survival of the Elderly [13], better sleep and academic performance in teens [14], increased vitamin D levels, improvement of neck bone mineral density in adults who already had osteoporosis [15], longer length of telomeres in women [16], decreased depression in the Elderly [17], lower risk of fatty liver [18], lower risk of aggressive prostate cancer [19], prevention of colon cancer [20], reduced incidence of gestational diabetes and premature births [21], longevity [22], and improvement of arthritis symptoms [7].…”
Section: Special Features Of the Mediterranean Diet And Links To Disementioning
confidence: 99%
“…In fact, data from 2010 to 2015 collected through Programa Aliméntate Sano (www.alimentatesano.cl), an open-access online platform created and led by our institution to provide general lifestyle (including the MedDiet) and health information and resources to the Chilean population, indicate that Chilean adults who exhibit higher adherence to MedDiet (based on a locally developed and validated score) [42] have a lower prevalence of overweight, obesity, and MS [43]. Furthermore, this cross-sectional study suggests that even small improvements in adherence to MedDiet may be associated with a significant decrease in obesity/overweight and MS, though this claim requires further testing.…”
Section: Mediterranean Diet Style In Chilementioning
confidence: 99%